Effect of High Temperature and High Pressure of Water on Micro-Characteristic and Splitting Tensile Strength of Gritstone - Zhao, Yu; Bi, Jing; Zhou, Xiaoping; Huang, Yansen (Frontiers in Earth Science, 2019)
To investigate the role of gritstone after hydro-thermal treatment on the mechanical properties and deformation failure behavior, the Brazilian test are carried out on gritstone specimens. Using load–displacement curves, the peak load and peak displacement of the gritstone specimens are analyzed in detail. The mechanical parameters are closely related to the high temperature, high pressure of water and the cooling down methods. The static splitting tensile strength (STSS) of specimens are decreasing with the increase of water pressure. In the cooling down group, the STSS and peak displacement of specimen WP1 are the lowest one. While, the STSS of specimen W1 is the biggest one. The differences in mechanical properties of the gritstone specimen are mainly caused by the ablation effect in the microscale under different HTHP and cooling down conditions. The surface deformation characteristics of the tested gritstone specimens are investigated by analyzing the full strain field and the local strain concentration. In the gritstone specimen, the major principal strain is first concentrated in the bottom or the top of gritstone specimens where the crack is initiated. The small jump of local strain means crack initiation and propagation, while the fracture of strain gauge leads to strain mutation. The SEM results are discussed to describe the fracture mechanism of brittle gritstone after HTHP treatment.